Urgensi Pengelolaan Humas bagi Keberlangsungan Lembaga Pendidikan Islam - Isnaini, Isnaini (Matan : Journal of Islam and Muslim Society, 2025)
Public relations (PR) serves as an essential medium for shaping positive public opinion and increasing public trust in institutions, including Islamic educational institutions. In this context, PR acts as a bridge between the institution and the public to foster mutual understanding, trust, and a positive image. Effective PR management supports the smooth implementation of the learning process and the improvement of educational quality by establishing harmonious two-way communication between the institution and the community. This study employs a qualitative approach using interviews and literature review methods to obtain relevant and in-depth data. The findings indicate that PR plays a strategic role in maintaining the sustainability of Islamic educational institutions, particularly in communicating the institution's vision and mission, building synergy with the community, and managing institutional image professionally. In conclusion, well-planned and continuous PR management is a crucial factor in supporting the sustainability and development of Islamic educational institutions amid ongoing social dynamics.